Risk Factors Associated with Low Birth Weight among Deliveries at Bharatpur Hospital - Kandel, Kamal Prasad; Kafle, Sindhu (Journal of Nepal Health Research Council, 2017)
Background: Babies with a birth weight of less than 2500 grams, irrespective of the period of their gestation are termed as Low Birth Weight (LBW) babies. Despite consistent efforts to improve the quality of maternal and child health, more than twenty million low birth-weight (LBW) babies are born every year throughout the world. Though, the health situation of Nepal has improved substantially over the years, the low birth-weight (LBW) rate is still high. The objective of this study was to assess the proportion of low birth weight and identify the associated factors for low birth weight in a live born infant among the institutionally delivered newborns. Methods: A hospital based cross sectional study was conducted in Obstetrics and Gynaecology ward of Bharatpur hospital, Bharatpur, from 17th September to 4th October , 2012. Altogether 480 respondents were taken and respondents were mothers who had delivered newborns in Bharatpur hospital. Results: A total of 480 births occurred during the study period, of which 480 met the study criteria. Among which 9.4% were low birth weight and 90.6% were normal birth weight .Overall mean birth weight was found to be 2.96 kg. Out of total 9.4% newborns were weighing less than 2.50 kg and mean birth weight 2.96kg. Conclusions: This study suggests that there were several factors interplaying which lead to LBW babies; which are age of mother at delivery,weight gain by mother during pregnancy, short, low body mass index and hyperemesis gravidarum was the strongest predictor in this study.